Functional Characterization of Insect Chemoreceptors: Receptivity Range, Expression and Evolution - William B. Walker (Frontiers Research Topics, 2016)
Olfaction and taste are of critical importance to insects and other animals, since vital behaviours, including mate, food and host seeking, as well as predator and toxin avoidance, are guided by chemosensory cues. Mate and habitat choice are to a large extent determined by chemical signals, and chemoreceptors contribute accordingly to pre-mating isolation barriers and speciation. In addition to fundamental physiological, ecological and evolutionary consideration, the knowledge of insect taste and especially olfaction is also of great importance to human economies, since it facilitates a more informed approach to the management of insect pests of agricultural crops and forests, and insect vectors of disease. Chemoreceptors, which bind to external chemical signals and then transform and send the sensory information to the brain, are at the core of the peripheral olfactory and gustatory system and have thus been the focus of recent research in chemical ecology. Specifically, emphasis has been placed on functional characterization of olfactory receptor genes, which are derived from three large gene families, namely the odorant receptors, gustatory receptors and ionotropic receptors. Spatial expression patterns of olfactory receptors in diverse chemosensory tissues provide information on divergent functions, with regards to ecologically relevant behaviours. On the other hand, characterization of olfactory receptor activation profiles, or "deorphanization", provides complimentary data on the molecular range of receptivity to the fundamental unit of the olfactory sense. The aim of this Research Topic is to give an update on the breadth and depth of research currently in progress related to understanding the molecular mechanisms of insect chemoreception, with specific emphasis on the olfactory receptors.